Proof of the environmental circulation of veterinary drug albendazole in real farm conditions - Navrátilová, Martina; Raisová Stuchlíková, Lucie; Matoušková, Petra; Ambrož, Martin; Lamka, Jiří; Vokřál, Ivan; Szotáková, Barbora; Skálová, Lenka (Environmental pollution (Barking, Essex, 2021)
Anthelmintics, drugs against parasitic worms, are frequently used in livestock and might act as danger environmental microcontaminants. The present study was designed to monitor the possible circulation of common anthelmintic drug albendazole (ABZ) and its metabolites in the real agriculture conditions. The sheep were treated with the recommended dose of ABZ. Collected faeces were used for the fertilization of a field with fodder plants (alfalfa and clover) which served as feed for sheep from a different farm. The selective ultrasensitive mass spectrometry revealed surprisingly high concentrations of active ABZ metabolite (ABZ-sulphoxide) in all samples (dung, plants, ovine plasma, rumen content and faeces). Our results prove for the first time an undesirable permeation of ABZ metabolites from sheep excrement into plants (used as fodder) and subsequently to other sheep in real agricultural conditions. This circulation causes the permanent exposition of the ecosystems and food-chain to the drug and can promote the development of drug resistance in helminths.
Keywords: Veterinary Drugs; Anthelmintics; Albendazole; farmy; Sheep; anthelmintika; zvířata; Drug resistance; ekosystém; Fodder plant; Micropollutants; Farms; veterinární léky; ovce; Ecosystem; Benzimidazoles; albendazol; Animals